Analisis Lingkungan Kerja Terhadap Kinerja Karyawan Pada Pabrik Beras Jaya Subur Makmur (Studi Kasus Pabrik Jaya Subur Makmur) - Muhammad Nazarudin; Enjang Suherman (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Founded in 1986 in Gintungkerra village, Karawang, the Jaya Subur Makmur Rice Mill is an important economic pillar of the region. This research examines the influence of the work environment on employee performance, including physical conditions such as cleanliness, lighting, temperature and noise, as well as social aspects such as communication and support from superiors. This research uses a qualitative approach with observation, in-depth interviews with 35 employees from various departments. The research results show that an appropriate physical work environment and positive social relationships have a significant influence on employee performance. However, some complaints, such as uncomfortable room temperatures and a lack of exercise programs, indicate areas that need improvement. These findings provide management with insight into improving working conditions and employee productivity, as well as contributing to the company's overall success.